STRUCTURING PEDAGOGICAL KNOWLEDGE IN THE PROCESS PREPARING STUDENTS FOR THE SUMMER PEDAGOGICAL PRACTICE - N.V. Dolgaya (Academy of Cognitive and Natural Sciences, 2007)
The object, tasks, content of student's summer pedagogical practice are exposed in the article. It was considered the structure of pedagogical knowledge at process of student's training for summer pedagogical practice.